2021
DOI: 10.1016/j.bandl.2020.104904
|View full text |Cite
|
Sign up to set email alerts
|

Sequential adaptation effects reveal proactive control in processing spoken sentences: Evidence from event-related potentials

Abstract: Wie sich die Sprachwahrnehmung an ständig eingehende Informationen anpasst, ist eine Schlüsselfrage in der Gedanken-und Gehirnforschung. Die vorliegende Dissertation zielt darauf ab, zum Verständnis von Anpassungen an die Sprecheridentität und Sprachfehler während der Sprachverarbeitung beizutragen und unser Wissen über die Rolle der kognitiven Kontrolle bei der Sprachverarbeitung zu erweitern. Zu diesem Zweck wurden ereigniskorrelierte Potentiale (EKPs, englisch: event-related potentials, ERPs) N400 und P600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
(58 reference statements)
4
11
0
Order By: Relevance
“…We hypothesized that if the sentence-preceding face cues indicate a switch in speaker identity for the upcoming sentence, listeners would reorient their attention to the new speaker and activate additional resources in working memory. Meanwhile, cued speaker repetitions might "prime" previously activated resources for the person who continues speaking, that is, neural resources might be recruited and maintained in advance for processing the next sentence-similar to the sequential effects reported by Xu et al (2021). To sum up, after a speaker switch we expected larger P600 amplitudes after critical words in the current sentence irrespective of its correctness, as compared to a speaker repetition across consecutive sentences.…”
Section: The Present Studysupporting
confidence: 51%
See 4 more Smart Citations
“…We hypothesized that if the sentence-preceding face cues indicate a switch in speaker identity for the upcoming sentence, listeners would reorient their attention to the new speaker and activate additional resources in working memory. Meanwhile, cued speaker repetitions might "prime" previously activated resources for the person who continues speaking, that is, neural resources might be recruited and maintained in advance for processing the next sentence-similar to the sequential effects reported by Xu et al (2021). To sum up, after a speaker switch we expected larger P600 amplitudes after critical words in the current sentence irrespective of its correctness, as compared to a speaker repetition across consecutive sentences.…”
Section: The Present Studysupporting
confidence: 51%
“…To conclude, prior studies showed that the P600 is linked to cognitive control in language processing (e.g., Xu et al., 2021), and that the P600 is sensitive to stereotype‐driven speaker characteristics and error statistics in local environments (e.g., Xu et al., 2019) and to speaker‐specific communicative styles (Regel et al., 2010). Therefore, P600 variations can be invoked to assess speaker‐specific processing strategies based on newly learnt individual‐specific characteristics in error probability and to investigate effects triggered by speaker sequences in multi‐speaker situations that possibly engage cognitive control mechanisms.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations